2009
DOI: 10.1159/000235584
|View full text |Cite
|
Sign up to set email alerts
|

2′-Ethoxy-5′-Methoxy-2-(5-Methylthienyl)Chalcone Inhibits Collagen-Induced Protein Tyrosine Phosphorylation and Thromboxane Formation during Platelet Aggregation and Adhesion

Abstract: Subendothelial collagen supports platelet adhesion, activation, and thrombus growth at sites of vascular damage. Previous studies have shown that chalcones possess antiplatelet activity, but their mechanism of action is not fully understood. In this study, a recently synthesized chalcone, 2′-ethoxy-5′-methoxy-2-(5-methylthienyl)chalcone (EMMTC), was used to investigate chalcone effects on platelet aggregation and adhesion. We found that EMMTC potently inhibited collagen-induced platelet aggregation with an IC<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…The Panel notes that the presence of chalcone and coumarin compounds in the NF could have an impact on coagulation, which is in line with observations in the submitted 90‐day study. Chalcones have been shown to inhibit thromboxane formation and exhibit antiplatelet activity (Ko et al., 2004 ; Lin et al., 2001 ; Lo et al., 2009 ). Xanthoangelol, one of the two major chalcones in ashitaba plant, has demonstrated antiplatelet activities in vivo (Ohkura et al., 2016 ).…”
Section: Assessmentmentioning
confidence: 99%
“…The Panel notes that the presence of chalcone and coumarin compounds in the NF could have an impact on coagulation, which is in line with observations in the submitted 90‐day study. Chalcones have been shown to inhibit thromboxane formation and exhibit antiplatelet activity (Ko et al., 2004 ; Lin et al., 2001 ; Lo et al., 2009 ). Xanthoangelol, one of the two major chalcones in ashitaba plant, has demonstrated antiplatelet activities in vivo (Ohkura et al., 2016 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Their results suggested that AA triggers platelet aggregation by inducing TXB2 activation; however, EMMTC or indomethacin (COX inhibitors) abolished this process. 151 Accordingly, PAF activates the AA metabolic pathway to produce various products, such as PG and TXA2, and the PAF–AA–PG/TXA2 signalling pathway is formed. PG and TXA2 are both AA metabolites, and these derivatives have important regulatory roles in inflammatory responses, glucose metabolism and lipid metabolism, which are associated with the development and progression of many diseases, such as diabetes, hypertension and obesity.…”
Section: Paf-mediated Cytokine Involvement In Nafldmentioning
confidence: 99%
“…These chalcones have demonstrated antioxidant, anti-inflammatory, antiangiogenic, antidiabetic and anti-obesity properties. Furthermore, they have been shown to inhibit platelet aggregation, induce apoptosis in cancer cells and suppress differentiation of preadipocytes to adipocytes [4][5][6][7][8][9][10]. Xanthoangelol, one of the flavenoid chalcones may improve lipid metabolism in the serum and the liver resulting in decreased risk of atherosclerosis and suppression of hepatic lipid accumulation [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%